Learning growth and development of living things topic: An analysis of students’ interest at a private middle school in Labuhanbatu district - Sari, Ayu Manja; Harahap, Hasmi Syahputra (Universitas Islam Negeri Sumatera Utara, 2023)
Students’ engagement and curiosity in learning Biology is suboptimal, hence innovative teaching methods are required to cultivate their interest and enhance their understanding of the subject matter. The research aims to identify differences in students’ interest in learning Biology across grades VII, VIII, and IX, based on gender and other indicators. The study analyzes the variations in students’ interest in the growth and development of living creatures at Bulu Tolang Adventist Private Middle School, Labuhanbatu Regency. The research population comprises all students at the school, with a research sample of 64 students using total sampling techniques. The study employed a quantitative descriptive research method and used a questionnaire of 20 statements calculated using a Likert scale. The data analysis involved descriptive description of the average percentage of students’ interest in learning. The research results revealed that: (1) Grade VII students’ interest in learning was categorized as high (65.62%), Grade VIII high (62.69%) and Grade IX medium (51.60%); (2) Students’ interest in learning based on gender showed that males were in the medium category (54.28%) in paying attention to lessons, while females were higher (65.23%); and (3) Student interest in learning based on indicators, namely feelings of enjoyment in participating in learning amounting to (59.68%), attention (58.99%), interest (57.43%), and student involvement (60.11%). The study concludes that Grade VIII students exhibit higher interest in learning Biology than their Grade VII and IX counterparts. Based on gender, female students demonstrate greater interest in learning than male students. The study also indicates that students’ feelings of joy, attention, interest, and involvement are in the medium category. Factors that influence the level of student learning include the family environment, motivation, and interest in learning. Innovative teaching methods can help support students’ higher interest in learning, including interest and feelings of enjoyment in learning.